Odpowiedzi

2009-11-17T16:45:17+01:00
A) x³-7x²-4x+28=0
x²(x-7)*-4(x-7)=0
(x-7)(x²-4)=0
x-7=0 lub x²-4=0
x=7 lub (x+2)(x-2)=0
x=7 lub x+2=0 lub x-2=0
x=7 lub x=-2 lub x=2

b) (x²+3x)(x²+4)(x²+4x+4)=0
x(x+3)(x²+4)(x+2)²=0
x=0 lub x+3=0 lub x²+4=0 lub x+2=0
x=0 lub x=-3 lub x=-2 (x²+4=0 wykluczamy, gdyż x²=-4 => x∈zbioru pustego)

Rozwiąż nierówności:
a) -2x⁴-4x³+6x²≤0 /×(-1)
2x⁴+4x³-6x²≥0
x²(2x²+4x-6)≥0
x² ≥0 lub 2x²+4x-6 ≥0
x ≥0 lub 2x²+4x-6 ≥0

Δ=16+48=64
√Δ=8
x₁=(-4-8):4=-12:4=-3
x₂=(-4+8):4=4:4=1
x≥-3 lub x≥0 lub x≥1

b)x³-3x²-4x+12>0
x²(x-3)*-4(x-3)>0
(x-3)(x²-4)>0
x-3>0 lub x²-4>0
x>3 lub (x-2)(x+2)>0
x>3 lub x-2>0 lub x+2>0
x>3 lub x>2 lub x>-2
1 5 1